Redução do preconceito racial: uma investigação analítico-comportamental - Mizael, Táhcita Medrado (Universidade Federal de São Carlos, 2019)
This doctoral dissertation was written in the form of manuscripts for publication and it is composed by a summary of the dissertation with less technical language, a theoretical essay and three experiments. In the essay, a review of behavior-analytic perspectives on prejudice was carried out and then, a critical analysis, pointing research questions with the aim of demonstrating the field’s contributions as well as highlighting paths for studying it. In the three experiments, children aged from 8 to 10, who related faces of White individuals with a positive symbol and/or faces of Black individuals with a negative symbol were recruited and trained to relate, indirectly, Black faces with the positive symbol, using the matching-to-sample procedure on Studies 1 and 2 and a respondent-type training procedure on Study 3. The aims were: to evaluate the formation and maintenance of equivalence classes on Study 1; to check the effectiveness of different training and testing parameters (mixed training of baseline relations, symmetry tests after training each baseline relation, and feedback reduction training before testing for equivalence) on the formation and maintenance of equivalence classes between a positive symbol and faces of Black people on Study 2; and to evaluate the effectiveness of a respondent-type training procedure on the formation of equivalence classes between a positive symbol and faces of Black individuals. In Study 1, 10 of 12 participants recruited formed the classes, that is, start relating the Black faces with the positive symbol after training. These results were maintained for 50 to 75% of participants six weeks after being initially tested for equivalence. Additionally, the number of selections of Black faces given the negative symbol was greatly reduced, from 61 times on pretest to four on posttest. On Study 2, 33 of 46 participants recruited formed the classes. From these, 75 to 81% participants maintained at least one of the equivalence relations on the maintenance test. More participants: a) formed the classes when the symmetry tests were used, and b) maintained those performances when the feedback reduction training was employed. Only six participants from the 12 recruited on Study 3 formed the classes after being exposed to a respondent-type training procedure. Taking into account the results from the three experiments, we suggest the use of all three parameters abovementioned with the matching-to-sample procedure for better results of equivalence class formation and maintenance. Finally, we highlight the scientific and social relevance of these studies and the possibilities of using these findings on future applications.
Racial prejudice reduction: a behavior-analytical investigation
Keywords: Preconceito racial; Equivalência de estímulos; Treino tipo-respondente; Manutenção de classes de equivalência; Viés racial; Redução do preconceito; Racial prejudice; Stimulus equivalence; Respondent-type training; Maintenance of equivalence classes; Racial bias; Prejudice reduction; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL